A contribuição do estruturalismo latino-americano na Lei de Thirlwall (1979) - Coutinho, Mônica Heloisa (2017)
The study in question is in line with the development and history of economic thought and its main theme is the search for an understanding of the currents of thought and of the main authors that influenced the reasoning developed by the post-keynesian author Antony P. Thirlwall. To that end, it is based on the conception that some concepts used by the author and post-Keynesian theorists of long-term growth would bear similarities to the ideas of the Economic Commission for Latin America and the Caribbean (ECLAC) developed in the 1950s and 1960. The objective is to analyze the extent to which the authors of ECLAC have influenced the reasoning developed by the post-Keynesian author Antony P. Thirlwall. To do so, the classic works and contributions of the main authors of structuralist theory and post-Keynesian theory will be recovered. Thus, this paper seeks to test the hypothesis that ECLAC thought influenced, to some extent, the work of Thirlwall, seeking to demonstrate from the exposition of the same, its equivalence. The hypothetical deductive method will be used, through a careful bibliographical review.